ANALISIS DETERMINAN KUALITAS HIDUP WARGA BINAAN: STUDI PADA RUTAN KELAS IIB PASANGKAYU - Tri Ahmad Setiawan; Obed Bida; Nani Harlinda Nurdin (Halu Oleo University, 2025)
Motivation on the quality of life of inmates at Pasangkayu Class IIB Detention Centre. The study used a quantitative approach with a survey-based causal-comparative design. A sample of 148 inmates was determined through simple random sampling. Data were collected through a Likert-scale questionnaire and analysed using Partial Least Squares–Structural Equation Modelling (PLS-SEM). The results showed that service quality had a significant positive effect on the quality of life of inmates (β = 0.269; p = 0.006), indicating the importance of adequate and humane services in improving the physical and psychological well-being of inmates. Motivation was the most dominant factor influencing quality of life (β = 0.524; p = 0.000), confirming the important role of internal and external motivation in building inmates' readiness to participate in the rehabilitation program. In contrast, the reintegration program did not have a significant effect on quality of life (β = 0.178; p = 0.078), which was caused by delays in implementation time and less than optimal relevance. Simultaneously, the three variables contributed 86.1% to inmates' quality of life (R² = 0.861). This finding underscores the need for comprehensive correctional management with improved services, reintegration programs from the beginning of their sentence, and motivational strategies to improve inmates' quality of life and better prepare them for their return to society.